Savonarola's women: visions and reform in Renaissance Italy - Herzig, Tamar (University of Chicago Press, 2008)
Girolamo Savonarola and his women followers -- "The chain of succession" : Colomba Guadagnoli and her saintly emulators -- The prophet's following in his own town : Savonarolism in Ferrrara -- The power of visions : Lucia Brocadelli and Osanna Andreasi -- The crisis years : 1505-1518 -- Recuperation and decline